EVALUASI SISTEM INSENTIF UNTUK MENINGKATKAN PERFORMANSI KERJA (STUDI KASUS: PEGAWAI NON AKADEMIK) - Atya Nur Aisha; Yassierli Yassierli; Pamoedji Hardjomidjojo (Jurnal Ilmiah Teknik Industri, 2014)
Employee is one of the main assets that support the success of an organization, so their performance will affect performance of the organization as a whole. This study aims to evaluate the application and determine the effect of incentive systems and other factors on job performance. Methods of data collection in this study consists of literature review, interviews and collecting questionnaires. A total of 103 questionnaires distributed to nonacademic employees at an educational institution. Data processing in this study, among others, evaluation of incentives satisfaction, correlation test using Pearson and Partial Least Squares (PLS) to predict the relationship between the variables. The results showed that salaries are the most important priority to be obtained at work. Relationships between variables in terms of a significant correlation between the variable conditions of employment, the willingness achievers, and incentives for job performance variables. In the design of the proposed incentives, provision of incentives aimed at increasing productivity and work motivation, maintaining equality and feasibility at incentives, and maintaining the welfare of employees. In addition, the design of proposed incentives gives adjustment to the amount of family allowance, responsibility allowance, general allowance, as well as performance benefits.